Vegetation History and Survival Patterns of the Earliest Village on the Qinghai–Tibetan Plateau - Gao, Jingyi; Hou, Guangliang; Xiao, Yongming; E, Chongyi; Wei, Haicheng; Sun, Yongjuan; Sun, Manping; Xue, Hongpan; Wende, Zhuoma; Jin, Sunmei; Chen, Xiaoliang (Frontiers in Plant Science, 2022)
The upper Yellow River valley in the northeastern Qinghai–Tibetan Plateau (QTP) is an important corridor for prehistoric migration to the hinterland plateau. However, most studies have focused on the Neolithic Age, with limited evidence for earlier periods. The Shalongka (SLK) site on the northeastern QTP spans the Epipaleolithic to Bronze Age and contains cultural deposits, so provides a good basis for unraveling the evolutionary history of the human–land relationship. In this study, we sampled the 420-cm-thick section T1406E at the SLK site and undertook lithologic stratigraphic description and analysis of grain size, redness, magnetic susceptibility, geochemical elements, pollen and charcoal. Dating control was provided by accelerated mass spectrometry 14C and optically stimulated luminescence methods. Results show that SLK site was affected by the local fluvial sedimentary environment. The absolute dating results of the SLK site have revealed that humans occupied the site during the Epipaleolithic (8.5–7.3 cal ka BP), Yangshao culture (5.9–5.1 ka) and Qijia Culture (4.1–3.9 cal ka BP). Pollen analysis showed that the humans lived in a landscape that was predominated by forest–steppe. Consolidating with multidisciplinary evidence, we learned that Epipaleolithic sites were occupied by microlithic hunter–gatherers and comprised by relatively fixed seasonal central campsites, and their mobility was significantly decreased from the early to late period. Subsequently, farmers of the Yangshao culture migrated from the low elevation (Chinese Loess Plateau) to the upper Yellow River valleys on the QTP and founded the earliest settlement villages (~5.9 ka) on the QTP. People of the Qijia culture adopted diversified survival strategies under the settled lifestyle. In all, we infered that SLK site may play an important role in the communication and integration between different people and cultures.